Indonesian EFL Learners’ Perceptions of Pedagogical Tasks Designed Based on Task Complexity - Mahpul; Khairun Nisa; Aksendro Maximilian (GHAITSA : Islamic Education Journal, 2026)
With reference to the Triadic Componential Framework, there are three aspects of designing pedagogical tasks to take into consideration, i.e., cognitive factors (task complexity), interactive factors (task condition), and learner factors (task difficulty). So far, numerous task-based studies have been concerned with investigation of the effect of tasks sequenced on the basis of cognitive factors. This is due to the fact that cognitive factors can be easily predicted from the beginning. Few studies have explored learner factors regarding levels of difficulty, stress, self-confidence, interest, and motivation contributing to language performance when learners work on the tasks manipulated along with the cognitive factors. The current study aimed to explore i) the Indonesian EFL learners’ perceptions of the three types of tasks developed on the basis of cognitive factors, and ii) the factors contributing to learners’ factors when performing the tasks. The subjects of the current study were 30 students of the English Department, the University of Lampung, Indonesia. Three types of tasks and questionnairs were used as the instruments to collect the data of learners’ affective factors. The findings of the current study showed that learner factors do not necessarily correspond to the manipulation of task complexity. This suggests that factors other than cognitive factors are necessarily taken into account of designing pedagogical tasks from the beginning as they contribute to learners’ performance of working on tasks.